PERHITUNGAN LUAS PENULANGAN METODE BISECTION PADA KOLOM BIAXIAL MENGGUNAKAN DELPHI DENGAN RUMUS BRESLER - Kamaludin Kamaludin (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2017)
One of the roles of technology in the field of engineering is in the field of structural engineering in designing an element in a concrete structure. Effective area of reinforcement on elements column is one that must be considered in planning a concrete structure. The stage of designing reinforcement often requires a fairly long process complicated and repetitive to get the balance requirements. There are several cases in designing reinforcement in concrete structures that are difficult to design if done manually because it requires a long and repetitive process. Seeing this situation requires a way to implement software technology on biaxial column reinforcement design. Software creation usually uses a numeric methods to facilitate implementation into programming languages. Problems what arises is how to apply numerical methods to solve problems the design problem of this biaxial column reinforcement, then one or several methods are needed numerical will be applied to the completion of the reinforcement design on the biaxial column element this is by utilizing software engineering technology. Case studies that will done in this study is the reinforcement design needed to withstand the load outside which is quite effective and efficient. The results of this study include the first, determining reinforcement area is faster and more accurate. Second, the error results obtained in determine this concrete reinforcement can be arranged as small as possible from the given tolerance value. Third, the area of reinforcement obtained in general is only a few iterations. Fourth, The application of the method for two (bisection) can be used in determining the area of reinforcement in a biaxial column because this method always converges to the actual value of the reinforcement.